Challenges And Solutions In Implementing The Teacher Code Of Ethics - Fitriyani; Fadillah Putri Ansyah; Agung Aris Munandar Aris Munandar; Tiara Aprilia; Malikul Sahhan; Nabil Al Bukhori (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
A professional teacher upholds the educational code of ethics when facing challenges. The code of ethics is very important in improving the professionalism of educators. Because it functions as a guide for all their behavior, the code of ethics helps regulate and enhance teachers’ attitudes, ethics, and morals. The implementation of the teacher’s code of ethics is a concrete effort by educators to demonstrate professional, moral, and responsible behavior in carrying out their duties. The code of ethics is not merely a written rule but a guideline that directs the attitudes and actions of teachers in every educational interaction. Through the code of ethics, teachers are expected to display exemplary character for students, reflecting personal integrity, honesty, and a commitment to improving the quality of education. The main objective of implementing the Teacher’s Code of Ethics is to create a conducive, integrity-based learning environment that supports students’ overall development. The challenges faced by teachers that they have not yet resolved in carrying out their educational duties can be divided into two categories: problems originating from the teachers themselves (internal problems) and those coming from outside the teachers (external problems). To address these issues, several solutions can be implemented, including strengthening the socialization and periodic training of the code of ethics for teachers, integrating ethical values into continuous professional development (CPD) programs, as well as enhancing supervision and moral guidance by school principals and supervisors.